2021
DOI: 10.32964/tj20.8.527
|View full text |Cite
|
Sign up to set email alerts
|

Can carbon capture be a new revenue opportunity for the pulp and paper sector?

Abstract: Transition towards carbon neutrality will require application of negative carbon emission technologies (NETs). This creates a new opportunity for the industry in the near future. The pulp and paper industry already utilizes vast amounts of biomass and produces large amounts of biogenic carbon dioxide. The industry is well poised for the use of bioenergy with carbon capture and storage (BECCS), which is considered as one of the key NETs. If the captured carbon dioxide can be used to manufacture green fuels to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In the end, the deciding factor between these different options for configuration and design of the capture plant will be the expected technoeconomic performance, which in turn depends on the future value of the captured biogenic CO 2 , the lignin product, as well as electricity and fuel prices. As thoroughly discussed and investigated by Kuparinen et al (2021) and Kuparinen et al (2023), the value of the captured biogenic CO 2 depends on future markets for green products that can be synthesized from the CO 2 (e.g., methanol), or the value of carbon removal credits. In the case of using CO 2 for carbon removals (negative emissions), it has also been shown that even though costs for capture and liquefaction dominate the costs for CCS, transport logistics and infrastructure are also deciding factors in the techno-economic evaluation of CCS (Karlsson et al, 2023).…”
Section: Figurementioning
confidence: 99%
“…In the end, the deciding factor between these different options for configuration and design of the capture plant will be the expected technoeconomic performance, which in turn depends on the future value of the captured biogenic CO 2 , the lignin product, as well as electricity and fuel prices. As thoroughly discussed and investigated by Kuparinen et al (2021) and Kuparinen et al (2023), the value of the captured biogenic CO 2 depends on future markets for green products that can be synthesized from the CO 2 (e.g., methanol), or the value of carbon removal credits. In the case of using CO 2 for carbon removals (negative emissions), it has also been shown that even though costs for capture and liquefaction dominate the costs for CCS, transport logistics and infrastructure are also deciding factors in the techno-economic evaluation of CCS (Karlsson et al, 2023).…”
Section: Figurementioning
confidence: 99%